Impact on urinary oxalate levels with use of ezetimibe. Issue 2 (4th January 2021) - Trautman, Christopher L.; Van Cleve, Margaret; Sullivan, Emily A.; Ball, Colleen T.; Cochuyt, Jordan J.; Porter, Ivan
Abstract: Background: Calcium oxalate stones are the most common cause of nephrolithiasis in the United States. Smaller studies of <15 patients investigating ezetimibe, a selective cholesterol absorption inhibitor, have suggested increased urine oxalate levels with use of the drug. We attempt to better define this relationship of ezetimibe on urinary oxalate using a larger patient sample analysing multiple urine collections on and off treatment. Materials and Methods: We retrospectively reviewed all consecutive patients from 01/2018 through 04/2019 evaluated for nephrolithiasis with use of ezetimibe documented in their medical record at Mayo Clinic Florida. Primary outcomes included increase in urinary oxalate with use of ezetimibe and reduction in urinary oxalate with discontinuation of medication. Results: Of 57 reviewed patients, 30 (53%) met inclusion criteria yielding 117 24‐h urine measurements either on ezetimibe (72 measurements) or off ezetimibe (41 measurements). The mean urinary oxalate level off ezetimibe was 39.86 mg versus 40.45 mg with ezetimibe. After adjusting for age and sex, the estimated difference was 1.239 mg (95% CI, −4.856 to 7.335 mg; p  = 0.93). A subset of six patients with urinary oxalate values both on and off ezetimibe showed a difference in 24‐h urinary oxalate levels ranged from −16.40 to 14.95 mg (mean difference = 0.93 mg; median difference = 3.84 mg). Conclusion: Use of ezetimibe does not provide clear evidence of a difference in urinary oxalate levels. Abstract : We attempt to better define this relationship of ezetimibe on urinary oxalate using a larger patient sample analyzing multiple urine collections on and off treatment. Use of ezetimibe does not provide clear evidence of a difference in urinary oxalate levels.